Fetal and neonatal adipose maturation: a primary site of cytokine and cytokine-receptor action. (May 2001) - Stephenson, T.; Budge, H.; Mostyn, A.; Pearce, S.; Webb, R.; Symonds, M. E.
Abstract : During late gestation, the maturation of fetal adipose tissue is geared towards the synthesis of high levels of uncoupling protein 1 (UCP1), which is unique to brown adipose tissue. At birth, rapid activation of UCP1 ensures a large increase in heat production. These adaptations are nutritionally sensitive, and may be mediated in part by rapid changes in prolactin and leptin secretion after birth. Restriction of maternal nutrition reduces adipose tissue deposition, with no effect on UCP1. Increased maternal food intake results in increases in levels of UCP1 and the short form of the prolactin receptor, but in a decrease in adipose tissue content per kg of fetus. The ontogeny of the long and short forms of the prolactin receptor follows that of UCP1, to peak at birth. Then, during postnatal life, UCP1 disappears in parallel with the loss of prolactin receptors. Treatment of neonatal lambs with prolactin increases body temperature and the thermogenic potential of brown adipose tissue. In contrast, acute leptin treatment results in maintenance of colonic temperature, but chronic leptin treatment accelerates UCP1 loss. Increasing our understanding of the interaction between prolactin and leptin during perinatal development may enable the establishment of strategies aimed at maximizing adipose tissue development in order to promote metabolic adaptation to the extra-uterine environment.